ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN DENGAN MENGGUNAKAN REGRESI LOGISTIK BINER - Tabah Heri Setiawan; Aden Aden; Anita Fujia (MathVisioN, 2022)
Customer satisfaction is something that must be a priority for every company, especially in Indomaret Ahmad Dahlan 02. In customer satisfaction, there are many factors that influence it, namely service factors, product quality, price, cost and emotional. This study aims to determine the binary logistic regression model associated with factors that affect customer satisfaction Indomaret Ahmad Dahlan 02 and to determine factors that can significantly affect customer satisfaction Indomaret Ahmad Dahlan 02. The analytical method used is binary logistic regression analysis with 5 independent variables, namely Service , Product quality , Price , Cost and Emotional . Based on the results of the study, the best model was obtainedThe logistic regression model can be concluded that the independent variable has a positive and significant effect on customer satisfaction is service quality.